Value Added Tax the Internet Trading: Features of Documentation, Accounting and Reporting - O. A. ZORINA; O. A. YURCHENKO; O. V. PETRAKOVSKA (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2022)
The scientific article reveals the peculiarities of documenting the value added tax calculations (hereinafter - VAT) in online commerce. The rules for filling in tax invoices and calculating adjustments to them in accordance with changes in the current tax legislation have been clarified.